A meta-review of stress, coping and interventions in dementia and dementia caregiving. Issue 1 (December 2016) - Gilhooly, K.; Gilhooly, M.; Sullivan, M.; McIntyre, A.; Wilson, L.; Harding, E.; Woodbridge, R.; Crutch, S.
Abstract Background There has been a substantial number of systematic reviews of stress, coping and interventions for people with dementia and their caregivers. This paper provides a meta-review of this literature 1988-2014. Method A meta-review was carried out of systematic reviews of stress, coping and interventions for people with dementia and their caregivers, using SCOPUS, Google Scholar and CINAHL Plus databases and manual searches. Results The meta-review identified 45 systematic reviews, of which 15 were meta-analyses. Thirty one reviews addressed the effects of interventions and 14 addressed the results of correlational studies of factors associated with stress and coping. Of the 31 systematic reviews dealing with intervention studies, 22 focused on caregivers, 6 focused on people with dementia and 3 addressed both groups. Overall, benefits in terms of psychological measures of mental health and depression were generally found for the use of problem focused coping strategies and acceptance and social-emotional support coping strategies. Poor outcomes were associated with wishful thinking, denial, and avoidance coping strategies. The interventions addressed in the systematic reviews were extremely varied and encompassed Psychosocial, Psychoeducational, Technical, Therapy, Support Groups and Multicomponent interventions. Specific outcome measures used in the primary sources covered by the systematic reviews were also extremely varied but could be grouped into three dimensions, viz ., a broad dimension of "Psychological Well-Being v. Psychological Morbidity" and two narrower dimensions of "Knowledge and Coping" and of "Institutionalisation Delay". Conclusions This meta-review supports the conclusion that being a caregiver for people with dementia is associated with psychological stress and physical ill-health. Benefits in terms of mental health and depression were generally found for caregiver coping strategies involving problem focus, acceptance and social-emotional support. Negative outcomes for caregivers were associated with wishful thinking, denial and avoidance coping strategies. Psychosocial and Psychoeducational interventions were beneficial for caregivers and for people with dementia. Support groups, Multicomponent interventions and Joint Engagements by both caregivers and people with dementia were generally found to be beneficial. It was notable that virtually all reviews addressed very general coping strategies for stress broadly considered, rather than in terms of specific remedies for specific sources of stress. Investigation of specific stressors and remedies would seem to be a useful area for future research.